2015
DOI: 10.16965/ijar.2015.237
|View full text |Cite
|
Sign up to set email alerts
|

Aplasia of Frontal Sinus: Ct Study

Abstract: The paranasal sinuses are subject to large variety of lesions. Congenital malformations and normal anatomic variations are important in this region To find out prevalence of frontal sinus aplasia in normal healthy population and to discuss its clinical importance. Materials and Methods: A cross-sectional analysis is performed on CT scans of head & neck region of patients visiting Radio-diagnosis Department of Era's Lucknow Medical College. Results: Frontal sinus aplasia was observed in 6.6% of target populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Our findings were very similar to Aydinlioglu et al and Sarita Choudhary et al who also reported unilateral absence of frontal sinus more in females than in males. 3,6 Aydinlioglu et al (2003) in their retrospective study on CT scans of 1200 subjects reported unilateral absence in 4.8% subjects and bilateral absences in 3.8% of subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings were very similar to Aydinlioglu et al and Sarita Choudhary et al who also reported unilateral absence of frontal sinus more in females than in males. 3,6 Aydinlioglu et al (2003) in their retrospective study on CT scans of 1200 subjects reported unilateral absence in 4.8% subjects and bilateral absences in 3.8% of subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Search of literature revealed similar findings. 3,[6][7][8] But it was contradicting to Yoshino et al findings, who reported unilateral left frontal sinus absence (16.8%) was more common than in right side (4.9%). 9 In this study, the overall frequency of bilateral frontal sinus absence was 2.5%.…”
Section: Resultsmentioning
confidence: 99%
“…Forensic identification methods rely on evaluating the morphology of the present sinus, and the absence of the frontal sinus (ie agenesis or aplasia) can be problematic [33]. For bilateral absences, the rate was higher for females than for males [75][76][77][78]. Although the difference was statistically significant, it likely has little predictive value for estimating the sex of skeletal remains based on frontal sinus absence.…”
Section: Discussionmentioning
confidence: 99%
“…They grow at the age of seven or eight and mature after puberty. 2,3 After 20 years of age, the size of the sinuses remains unchanged until the atrophic changes begin to appear due to advancing age. 4 Frontal sinuses drain into the anterior part of the middle meatus of the nose through an ethmoid infundibulum or a frontonasal duct.…”
Section: Introductionmentioning
confidence: 99%